GAMBARAN GAYA HIDUP PADA PENDERITA HIPERTENSI DI PUSKESMAS II DENPASAR BARAT - Ni Made Ayu Damayanti; I Wayan Suardana; Neil Oktovianus Manafe; I Gede Yudiana Putra (Jurnal Kesehatan Medika Udayana, 2019)
Background: Hypertension has now become a global problem because its prevalence continues to increase along with lifestyle changes that include unhealthy habits. the aim is to find out a description of lifestyle in hypertensive patients in West Denpasar Health Center II. Method: The study design was descriptive with the Cross Sectional approach. The sample in this study were all hypertensive patients who were treated at the Denpasar Public Health Center II. The sampling technique is Acidental sampling with a sample of 46 respondents. The research instrument used was a questionnaire sheet. The results of data processing are presented in narrative form, frequency distribution tables are accompanied by interpretations. Results: Hypertension sufferers in West Denpasar Health Center II were 27 respondents (58.7%) who did not have the habit of consuming excess salt; 26 respondents (56.5%) who did not have coffee consumption habits; 34 respondents (73.9%) who did not have the habit of consuming liquor; 32 respondents (69.6) did not have smoking habits; 26 respondents (56.5%) respondents did not have enough hours of rest / sleep; respondents who do sufficient activities / sports; 46 respondents as many as 25 respondents (54.3%) obeyed taking drugs; 25 respondents (54.3%) did not routinely carry out tension control; 30 respondents (65.2%) faced maladaptive stressors. Conclusion: To reduce the incidence of hypertension in patients with hypertension, health promotion programs to the public regarding hypertension factors need to be optimized.Keywords: Hypertension; Lifestyle